Exploring the role and therapeutic potential of RNA N6-methyladenosine modification in abortion disease pathology: a comprehensive review - Chang, Zhuo; Li, Lu-Hao; Lv, Liang-Zhen; Wang, Zhao-Di; Wang, Qing-yi; Zhu, Hui; Jiang, Bei; Zhou, Xue-Ming; Han, Ya-Peng; Pan, Xue; Ren, Li; Cheng, Sen; et al. (Frontiers in Genetics, 2026)
Recurrent spontaneous abortion (RSA), defined as two or more consecutive pregnancy losses, affects 1%–5% of couples and poses a significant challenge to reproductive health. Despite its prevalence, the underlying etiology remains elusive in approximately half of all cases, hindering the development of targeted therapies. The emerging field of epitranscriptomics, particularly the dynamic and reversible N6-methyladenosine (m6A) RNA modification, offers a novel lens through which to investigate the complex gene-environment interactions underlying RSA. This review systematically synthesizes current knowledge on the pivotal roles of m6A modification in key processes essential for a successful pregnancy: gametogenesis and early embryo quality, placental development and function, and the establishment of immune tolerance at the maternal-fetal interface. We critically evaluate the direct and indirect evidence linking dysregulation of specific m6A regulators to the pathophysiology of RSA, drawing from human tissue studies, RSA animal models, and insights extrapolated from related fields.Furthermore, we discuss the translational potential and considerable challenges of targeting the m6A machinery for therapeutic intervention in RSA. This review aims not only to summarize the current landscape but also to provide a critical framework to guide future mechanistic and clinical research in this promising area.